Individual and facility-level determinants of iron and folic acid receipt and adequate consumption among pregnant women in rural Bihar, India - Wendt, Amanda; Stephenson, Rob; Young, Melissa; Webb-Girard, Amy; Hogue, Carol; Ramakrishnan, Usha; Martorell, Reynaldo (PLOS ONE, 2015)
Background In Bihar, India, high maternal anemia prevalence and low iron and folic acid supplement (IFA) receipt and consumption have continued over time despite universal IFA distribution and counseling during pregnancy. Purpose To examine individual and facility-level determinants of IFA receipt and consumption among pregnant women in rural Bihar, India. Methods Using District Level Household Survey (2007-08) data, multilevel modeling was conducted to examine the determinants of two outcomes: IFA receipt (any IFA receipt vs. none) and IFA consumption (≥90 days vs. <90 days). Individual-level and facility-level factors were included. Factor analysis was utilized to construct antenatal care (ANC) quality and health sub-center (HSC) capacity variables. Results Overall, 37% of women received any IFA during their last pregnancy. Of those, 24% consumed IFA for 90 or more days. Women were more likely to receive any IFA when they received additional ANC services and counseling, and attended ANC earlier and more frequently. Significant interactions were found between ANC quality factors (odds ratio (OR): 0.37, 95% confidence interval (CI): 0.25, 0.56) and between ANC services and ANC timing and frequency (OR: 0.68, 95% CI: 0.56, 0.82). No HSC factors were significantly associated with IFA receipt. Women were more likely to consume IFA for ≥90 days if they attended at least 4 ANC check-ups and received more ANC services. IFA supply at the HSC (OR: 1.37, 95% CI: 1.04, 1.82) was also significantly associated with IFA consumption. Conclusions Our findings indicate that individual and ANC factors (timing, frequency, and quality) play a key role in facilitating IFA receipt and consumption. Although HSC capacity factors were not found to influence our outcomes, significant variation at the facility level indicates unmeasured factors that could be important to address in future interventions.
Gesehen am 30.06.2020